Imaginaries of the ideal migrant worker: a Lacanian interpretation - Sergei Shubin (Environment and Planning D - Society and Space, 2014)
This paper draws on the ideas of Jacques Lacan to explore the production of “ideal” migrant workers by recruitment agencies in the context of Latvian labour migration to the UK. It argues that such "idealised" constructions hide inconsistencies and slippages implicit within the fabric of recruitment discourse and practice. The paper therefore studies the construction of subjectivity in a migration context (unconscious and conscious processes of identification) and explores the drawings, sketched by respondents during qualitative research conducted in Latvia to challenge stable expectations of labour migrants (the idea of stable selfhood) and labour migration. It concludes with conceptual observations about the complex process of identification.